2015
DOI: 10.1037/a0039105
|View full text |Cite
|
Sign up to set email alerts
|

So happy together? Predictors of satisfaction with supervision for play therapist supervisees.

Abstract: The present study examined current supervision experiences and factors that predicted satisfaction for play therapist supervisees. Participants (n = 238) from the Association for Play Therapy (APT) were included. Participants completed a web-hosted survey which included items related to their current supervision experience, the Supervisee Satisfaction Questionnaire (SSQ), and a demographic questionnaire. A nonexperimental, correlational design was used to examine the relationship between participants’ current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Supervision articles included three research articles and eight nonresearch articles. Of the three research articles on play therapy supervision, two studies investigated predictors of satisfaction (VanderGast & Hinkle, 2015) and preference of supervisees (VanderGast, Culbreth, & Flowers, 2010). One study investigated mindfulness in supervision (Glazer & Stein, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervision articles included three research articles and eight nonresearch articles. Of the three research articles on play therapy supervision, two studies investigated predictors of satisfaction (VanderGast & Hinkle, 2015) and preference of supervisees (VanderGast, Culbreth, & Flowers, 2010). One study investigated mindfulness in supervision (Glazer & Stein, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In regard to supervision articles, we found fewer research articles ( n = 3) and more nonresearch articles ( n = 8).Two quantitative research articles utilized survey data to explore supervisees’ experiences (VanderGast et al, 2010) and satisfaction (VanderGast & Hinkle, 2015) of play therapy supervision. One qualitative research article examined supervisors’ perceptions of play therapy supervision (Glazer & Stein, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in supervision has been cited as an important source of professional wellness for play therapists (Meany-Walen et al, 2018). VanderGast and Hinkle (2015) found that play therapists were more satisfied with the supervision process when they viewed their supervisors as having a play therapist professional identity. This suggests that play therapists may experience a sense of validation when working with a supervisor who understands what it is like to do the same type of work.…”
Section: Supervisionmentioning
confidence: 99%
“…Thus, supervision can help set the tone for a fulfilling career. Play therapy supervisors play an important role in orienting play therapists to the profession and in cultivating professional identity development (Garza et al, 2009; VanderGast & Hinkle, 2015). Engaging in supervision has been cited as an important source of professional wellness for play therapists (Meany-Walen et al, 2018).…”
Section: Play Therapists’ Job Satisfactionmentioning
confidence: 99%